PTEN Activation by DNA Damage Induces Protective Autophagy in Response to Cucurbitacin B in Hepatocellular Carcinoma Cells. (30th November 2016) - Niu, Yanan; Sun, Wen; Lu, Jin-Jian; Ma, Dik-Lung; Leung, Chung-Hang; Pei, Lixia; Chen, Xiuping
Abstract : Cucurbitacin B (Cuc B), a natural product, induced both protective autophagy and DNA damage mediated by ROS while the detailed mechanisms remain unclear. This study explored the mechanism of Cuc B-induced DNA damage and autophagy. Cuc B decreased cell viability in concentration- and time-dependent manners. Cuc B caused long comet tails and increased expression of γ -H2 AX, phosphorylation of ATM/ATR, and Chk1/Chk2. Cuc B induced autophagy as evidenced by monodansylcadaverine (MDC) staining, increased expression of LC3II, phosphorylated ULK1, and decreased expression of phosphorylated AKT, mTOR. Cuc B induced apoptosis mediated by Bcl-2 family proteins and caspase activation. Furthermore, Cuc B induced ROS formation, which was inhibited by N-acetyl-L-cysteine (NAC). NAC pretreatment dramatically reversed Cuc B-induced DNA damage, autophagy, and apoptosis. Cuc B-induced apoptosis was reversed by NAC but enhanced by 3-methyladenine (3-MA), chloroquine (CQ), and silencing phosphatase and tensin homolog (PTEN). 3-MA and CQ showed no effect on Cuc B-induced DNA damage. In addition, Cuc B increased PTEN phosphorylation and silence PTEN restored Cuc B-induced autophagic protein expressions without affecting DNA damage. In summary, Cuc B induced DNA damage, apoptosis, and protective autophagy mediated by ROS. PTEN activation in response to DNA damage bridged DNA damage and prosurvival autophagy.